The Impact of Training Towards Employees’ Performance at Santika Premiere Dyandra Hotel Medan - Efin Shu; Daniel Augustinus (Universitas Pelita Harapan Medan Campus, 2018)
The purpose of this research is to find out if the impact of training towards employees’ performance at Santika Premiere Dyandra Hotel Medan. The samples of this research are 38 Front of House employees. Sampling technique is incidental sampling which is a sample determination technique based on chance, i.e. anyone whom are accidentally/ incidentally met by the researcher can be used as a sample, when viewed as appropriate to be data source. Data analysis using quantitative descriptive with the model of Simple Regression test analysis, hypothesis test using coefficient of determination test (R2) and partial test (t test), while data processing using SPSS 2.2. Based on Partial Test (t test), the result of this research shows that partially, training has positive effects towards Front of House employees’ performance at Santika Premiere Dyandra Hotel Medan. However, based on Coefficient of Determination test (R2), training variable has a little impact towards performance variable at Santika Premiere Dyandra Hotel Medan. This is proven by the coefficient determination value of 0,092.Key words: training, performance, and Santika Premiere Dyandra Hotel Medan.